A SNaPshot Assay for Determination of the Mannose-Binding Lectin Gene Variants and an Algorithm for Calculation of Haplogenotype Combinations - Jana Mrazkova; Petr Sistek; Jan Lochman; Lydie Izakovicova Holla; Zdenek Danek; Petra Borilova Linhartova (Diagnostics, 2021)
Mannose-binding lectin (MBL) deficiency caused by the variability in the MBL2 gene is responsible for the susceptibility to and severity of various infectious and autoimmune diseases. A combination of six single nucleotide polymorphisms (SNPs) has a major impact on MBL levels in circulation. The aim of this study is to design and validate a sensitive and economical method for determining MBL2 haplogenotypes. The SNaPshot assay is designed and optimized to genotype six SNPs (rs1800451, rs1800450, rs5030737, rs7095891, rs7096206, rs11003125) and is validated by comparing results with Sanger sequencing. Additionally, an algorithm for online calculation of haplogenotype combinations from the determined genotypes is developed. Three hundred and twenty-eight DNA samples from healthy individuals from the Czech population are genotyped. Minor allele frequencies (MAFs) in the Czech population are in accordance with those present in the European population. The SNaPshot assay for MBL2 genotyping is a high-throughput, cost-effective technique that can be used in further genetic-association studies or in clinical practice. Moreover, a freely available online application for the calculation of haplogenotypes from SNPs is developed within the scope of this project.